Corps sensible, environnement urbain moderniste - Françoise Michel-Jones (Ateliers d'Anthropologie)
From the point of view of an anthropology of vision, this article explores the relationship between sensing body and urban environment, particularly the perceptive and cognitive changes that occurred in the West of the 1960s, as fascinatingly depicted by Jacques Tati in a film—Playtime—that became a cinema classic.A master of filmed description and analysis of the typical social gestures and behaviours of the urban middle classes, Jacques Tati offers a film intended as “audio-visual” film “material”, rather than a filmed account of a story centred on a subject. In it, he confronts his character Hulot with a transitionless shift from the familiar conventions of a historic capital (Paris), which make it possible to stroll peacefully, to the exhausting and deceptive signage and plastic and formal components of a big city that makes for a world in itself, with no space or time outside the frame: a city that asserts the international, modernist version of a city rather than its modern version, being ubiquitous and timeless, devoted to accelerated communication, circulation and consumption.Lost in a disappointing “quest” with multiplying loops and dead-ends, Hulot often appears to be dissolving—shadowless body—at the whim of avatars, doubles and reflections, despite the virtues of transparency and communication, considered to be linked with the “new” architectural and urban environment. Then the dwindling of the “me, of the subject, of the person” (Mauss) is manifested in the opacity and absurdity of the loss of meaning and negation of history that accompany the presumed “functional” requirement of the serial and the undifferentiated.